Internalization of Finnish small- and medium-sized enterprises providing professional services to Russia - Salii, Elena (2019)
The topic of this master‟s thesis is the entry of small- and medium-sized Finnish companies providing professional services, to the Russian market. Small- and medium-sized enterprises (SMEs) are the vital part of Finnish economy and Finnish export activities grow year by year. Since active research on internalization of service SMEs was initiated only two decades ago, the goal of this research is to gain an understanding of the process of internationalization, especially pathways Finnish SMEs providing professional services undertake, choice of entry mode and use of networks. Moreover, the researcher aims to provide practical guidelines for Finnish SMEs planning Russian market penetration: great attention is paid to characteristics and key challenges that Russian market carries. The research is conducted as a qualitative multiple case study. The researcher conducted nine different interviews: five with the Finnish SMEs engaged in the Russian business and four interviews with consultants that have extensive experience in Russian culture and ways of doing business. An abductive reasoning approach is followed in order to refine the existing literature and intertwine this current knowledge with empirical data. The research findings suggest that single theoretical framework (e.g. stage model of internalization) is not able to describe modern companies‟ decisions inside international activities as SMEs tend to combine and integrate several theoretical modes. Specifically for the Russian market, while it is considered as psychically distant market, business networks play vital role in establishing business operations. Desire to keep full control of operations, to be closer to the potential customers, to serve existing clients globally, and intangibility of the services Finnish SMEs provide, often stimulate them to set up a local subsidiary. However, unique characteristics and challenges Russian market and culture possess, might become a barrier to entry and business extension. Therefore, in addition to the recognition of these cultural and market differences, another goal of the research was to provide managerial implications for the service SMEs planning Russian market penetration.